2005
DOI: 10.1021/jf0518599
|View full text |Cite
|
Sign up to set email alerts
|

Sweet and Sour Cherry Phenolics and Their Protective Effects on Neuronal Cells

Abstract: The identification of phenolics from various cultivars of fresh sweet and sour cherries and their protective effects on neuronal cells were comparatively evaluated in this study. Phenolics in cherries of four sweet and four sour cultivars were extracted and analyzed for total phenolics, total anthocyanins, and their antineurodegenerative activities. Total phenolics in sweet and sour cherries per 100 g ranged from 92.1 to 146.8 and from 146.1 to 312.4 mg gallic acid equivalents, respectively. Total anthocyanins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

44
241
6
7

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(298 citation statements)
references
References 36 publications
44
241
6
7
Order By: Relevance
“…These values are higher than data reported by Khoo et al (2011) in 34 sour cherry cultivars, in the range from 74 to 754 mg/100 g of total polyphenols. Other previous reports on the total polyphenol content of sour cherries varied from 78 to 500 mg/100 g (Kim et al 2005, Bonerz et al 2007, Dragović-Uzelac et al 2009). Higher concentrations of polyphenols in our investigation as compared to other studies may be the result of differences in extraction and measuring protocols (Melicháčová et al 2010) performed by a group of several authors in polyphenol determination but also it can be a consequence of cultivar impact, climatic conditions and agricultural measures in specific location were sampling is done.…”
Section: Resultsmentioning
confidence: 88%
“…These values are higher than data reported by Khoo et al (2011) in 34 sour cherry cultivars, in the range from 74 to 754 mg/100 g of total polyphenols. Other previous reports on the total polyphenol content of sour cherries varied from 78 to 500 mg/100 g (Kim et al 2005, Bonerz et al 2007, Dragović-Uzelac et al 2009). Higher concentrations of polyphenols in our investigation as compared to other studies may be the result of differences in extraction and measuring protocols (Melicháčová et al 2010) performed by a group of several authors in polyphenol determination but also it can be a consequence of cultivar impact, climatic conditions and agricultural measures in specific location were sampling is done.…”
Section: Resultsmentioning
confidence: 88%
“…Studies using aged animals and aging models have reported that daily consumption of polyphenol-rich foods improves spatial learning and memory performance (Shukitt-Hale et al 2007;Williams et al 2008;Rendeiro et al 2009;Shukitt-Hale et al 2009a, b;Willis et al 2009;Rendeiro et al 2013). Because tart cherries contain a plethora of flavonoids and other phenolic compounds [ (Kim et al 2005), reviewed in (Ferretti et al 2010;McCune et al 2011)], and accumulate in the brain in a dose-dependent manner, it is not surprising that short-term intake of tart cherries led to improvement in spatial working memory.…”
Section: Discussionmentioning
confidence: 99%
“…Cyanidin is the major anthocyanin in tart cherries (Seeram et al 2001a) followed by flavan-3-ols and flavonols (Bhagwat et al 2014). Studies using cell lines, animal models, and humans demonstrated that the phytochemicals found in tart cherry confer health benefits by inducing cell-cycle arrest and apoptosis in precancerous and cancer cells (Kang et al 2003;Bobe et al 2006;Martin and Wooden 2012;Sehitoglu et al 2014), decreasing triglyceride and total cholesterol levels (Seymour et al 2008), reducing inflammation (Seeram et al 2001b;Tall et al 2004;Seymour et al 2009;Ou et al 2012), and decreasing oxidative stress (Kim et al 2005;Traustadottir et al 2009). Furthermore, a study by Kirakosyan showed that cherry anthocyanins accumulated in the brain of young rats after 3 weeks of feeding with either 1 or 10 % tart cherry-supplemented diets in a dose-dependent manner (Kirakosyan et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Shogaols, other fragments of ginger, have neural protective effects and also cause increasing intestinal blood flow (29). So it may be concluded that ginger facilitates the blood cycle between mother and embryo and that it causes better brain growth of the offspring.…”
Section: Discussionmentioning
confidence: 99%